"HPV? Never heard of it!": A systematic review of girls' and parents' information needs, views and preferences about human papillomavirus vaccination - Hendry, M; Lewis, R; Clements, A; Damery, S; Wilkinson, C (2013)
Background and objective: Two human papillomavirus vaccines were licenced in 2006/2007 for cervical cancer prevention. National vaccination programmes for schoolgirls were subsequently introduced in some European countries, North America and Australia. To understand factors influencing vaccine uptake and to inform the development of appropriate UK educational materials, we aimed to synthesise evidence of girls' and parents' information needs, views and preferences regarding HPV vaccination. Design: Systematic review and mixed method synthesis of qualitative and survey data. Data sources: Twelve electronic databases; bibliographies of included studies 1980 to August 2011. Review methods: Two reviewers independently screened papers and appraised study quality. Studies were synthesised collaboratively using framework methods for qualitative data, and survey results integrated where they supported, contrasted or added to the themes identified. Results: Twenty-eight qualitative studies and 44 surveys were included. Where vaccination was offered, uptake was high. Intention to decline was related to a preference for vaccinating later to avoid appearing to condone early sexual activity, concerns about vaccine safety and low perception of risk of HPV infection. Knowledge was poor and there were many misconceptions; participants tried to assess the potential benefits and harms of vaccination but struggled to interpret limited information about HPV in the context of existing knowledge about sexually transmitted infections and cancer.Conclusion Many girls and their parents have limited understanding to an extent that impinges on their ability to make informed choices about HPV vaccination and could impact on future uptake of cervical screening. This is a considerable challenge to those who design and provide information, but getting the messages right for this programme could help in developing patient information about other HPV related cancers. © 2013 Elsevier Ltd.